Expression of pathogenicity factors by Enterococcus strains isolated from inpatients with bloodstream infection in Belo Horizonte, Minas Gerais, Brazil - Samir de Deus E. Andrade; Amanda Maria P. Borges; Gustavo A. R. Duarte; Simone G. Santos; Luiz M. Farias; Paula P. Magalhães
ABSTRACT In this investigation, we addressed the pathogenicity profile of 35 Enterococcus samples isolated from inpatients with bloodstream infections (BSI) at hospitals in Belo Horizonte (MG), Brazil. The most prevalent species was E. faecalis (27/77.14%). The ability to produce gelatinase and cytolysin was detected in 14/40% of the samples and presented a heterogeneous distribution. Biofilm production was observed in 27 strains (77.14%) and classified as weak (8/22.86%), moderate (18/51.42%), or strong (1/2.86%). This study adds to knowledge of the pathogenicity profile of Enterococcus strains isolated from BSI, aiming to increase understanding about virulence of the circulating strains in Brazil.